ANALISIS PERISTIWA TUTUR PADA TRADISI MARSIHOL-SIHOL DI NAGORI BANDAR DOLOK KABUPATEN SIMALUNGUN: KAJIAN SOSIOLINGUISTIK - Butar Butar, Marlise Henjelina; Fahmy Dalimunthe, Syairal; Januarsyah Daulay, Muhammad Anggie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the form of speech events and social context in the Marsihol-sihol tradition through a sociolinguistic approach that focuses on the SPEAKING Dell Hymes theory. The method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The results of this study consist of the form of speech events and their social context. The form of speech events consists of a setting and scene that takes place at the parboru's house during the day with a formal, relaxed, serious and sad atmosphere. Participants consisted of the king of parhata, the bride and groom, parboru, paranak, tulang sibuea, dongan tubu, natua tua nihuta. Ends is a form of conveying the meaning of the arrival of the paranak to the parboru, the delivery of traditional food, advice and blessings, as well as the delivery of gratitude. Act sequences are delivered through a form of speech consisting of question sentences, commands, and statements to clarify the content of speech. Key is conveyed through speech in a relaxed tone, a serious tone and through body gestures. The delivery of instrumentalities is spoken orally using Toba and Indonesian Batak. Norms stipulate that speech participants can speak after being invited by the main speaker. Genres are conveyed through traditional conversations that contain prayers, prayers, and songs. Meanwhile, the social element in the speech event consists of thesocial association of the speaker which shows the kinship relationship of Dalihan Na Tolu. Social goals are to strengthen family ties, provide respect, instill social and cultural values, and carry out advice from the parboru. Social norms consist of religious norms and politeness that make speech participants begin their speech with gratitude to God and deliver speech with polite traditional greetings.